(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Epidemiological studies in recent years have pointed towards an environmental component in the outbreak of any disease or epidemic in various parts of the world. Owing to increasing urbanization that has come at the enormous cost of deforestation and changes in land use, we have come into closer interactions with the unknown world of microbes and bacteria that were previously contained in the wild. Northeast India is a species-rich region that falls within the Indo-Burma Biodiversity Hotspot, containing numerous indigenous tribes within it with varying cultures among them. The consumption pattern of species or the food habits, climate and frequent flooding has increased in the last few years at an alarming rate, heightening the risk of zoonotic diseases, examples of which include COVID-19, Ebola, and various strains of influenza. The present paper focuses on the probable outbreak of new pathogens in northeast India, and it also discusses the history of some pathogenic transmission in the region with factors favourable for new outbreaks.